Morphoproteomics, E6/E7 in-situ hybridization, and biomedical analytics define the etiopathogenesis of HPV-associated oropharyngeal carcinoma and provide targeted therapeutic options - Robert E. Brown; Syed Naqvi; Mary F. McGuire; Jamie Buryanek; Ron J. Karni (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Human papillomavirus (HPV) has been identified as an etiopathogenetic factor in oropharyngeal squamous cell carcinoma. The HPV E6 and E7 oncogenes are instrumental in promoting proliferation and blocking differentiation leading to tumorigenesis. Although surgical intervention can remove such tumors, the potential for an etiologic field effect with recurrent disease is real. A downstream effector of E7 oncoprotein, enhancer of zeste homolog 2 (EZH2), is known to promote proliferation and to pose a block in differentiation and in turn, could lead to HPV-induced malignant transformation. However, the EZH2 pathway is amenable to low toxicity therapies designed to promote differentiation to a more benign state and prevent recurrent disease by inhibiting the incorporation of HPV into the genome. This is the first study using clinical specimens to demonstrate EZH2 protein expression in oropharyngeal carcinoma (OPC). Methods The study included eight patients with oropharyngeal carcinoma, confirmed p16INK4a- positive by immunohistochemistry (IHC). The tissue expression of E6/E7 messenger RNA (mRNA) was measured by RNAscope® in-situ hybridization technology. Expression of EZH2, Ki-67, and mitotic indices were assessed by morphoproteomic analysis. Biomedical analytics expanded the results with data from Ingenuity Pathway Analysis (IPA) and KEGG databases to construct a molecular network pathway for further insights. Results Expression of E6 and E7 oncogenes in p16INK4a- positive oropharyngeal carcinoma was confirmed. EZH2 and its correlates, including elevated proliferation index (Ki-67) and mitotic progression were also present. Biomedical analytics validated the relationship between HPV- E6 and E7 and the expression of the EZH2 pathway. Conclusion There is morphoproteomic and mRNA evidence of the association of p16INK4a-HPV infection with the E6 and E7 oncogenes and the expression of EZH2, Ki-67 and mitotic progression in oropharyngeal carcinoma. The molecular network biology was confirmed by biomedical analytics as consistent with published literature. This is significant because the biology lends itself to targeted therapeutic options using metformin, curcumin, celecoxib and sulforaphane as therapeutic strategies to prevent progression or recurrence of disease.